Investment Interest and Consumptive Behaviour of Student Investors: Between Rationality and Irrationality - Umboh, Jandi Elriko; Atahau, Apriani Dorkas Rambu (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2019)
The purpose of this study is to examine the tendency to invest and consume among student in North Sulawesi. Phenomenon in North Sulawesi province showed an increase in the number of stock investors dominated by young investors (university students). In making investment decision, they often act in irrational way (herding behavior). In contrast, other phenomena demonstrated a consumptive behavior of those young investors which contradict with investment interests. Populations of this research are 3468 student investors at Indonesia stock Exchange Investment Gallery in the North Sulawesi province. Using accidental sampling, the sample selected is 250 student investors. The analytical technique used is Covariance Based Structural Equation Modeling (CB-SEM). The results showed that investment interest mediate the effect of herding behavior on consumptive behavior. It implies the need to educate student investors on the importance of minimizing the consumptive behavior